Capturing and Explaining Sensory Differences among Organically Grown Vegetable‐Soybean Varieties Grown in Northern California. Issue 3 (11th February 2019) - Flores, David; Giovanni, Maria; Kirk, Larry; Liles, Garret
Abstract: Vegetable soybean (VS), known as edamame, is appreciated for its robust flavor and exceptional nutrient content. Although the United States is one of the world's leading producers of soy, only a fraction is harvested as edamame. Research involving varietal differences is very limited, particularly among U.S. consumers. Sensory attributes of three VS varieties grown in Northern California (with organic methods) were assessed: Giant Midori (GM), ButterBean (BB), and Kuroshinja (KU). Participants ( n = 74) rated four characteristics: flavor, texture, appearance, and overall liking on unlabeled, 11‐point hedonic scales and were asked if they would purchase the variety. A small portion of these participants would again evaluate the varieties, using free choice profiling (FCP) methodology. After these evaluations, texture analyzer, colorimeter, and high‐performance liquid chromatography (free amino acids, sugars, and isoflavones) testing were performed. Among tested varieties, distinct differences in quality were found, with GM preferred first, followed by KU, and BB. GM was significantly harder, a more intense green, had more free sugars and isoflavones and fewer free amino acids, whereas KU and BB trended to be the opposite. Analyzing FCP data with a General Procrustes Analysis, varieties were separated in different factors for flavor and texture, but not appearance. Although repeated, and larger trials are needed, our study signifies that consumers are able to detect differences among VS varieties. Further research may influence producers to grow the variety likely to be most profitable and marketable.